(untitled) (Journal of Informatics and Mathematical Sciences, 2017)
The aim of this paper is to introduce a further generalization of compactness in soft generalized topological spaces. We define and study the concept of soft \(D_μ\)-compact spaces in soft generalized topological spaces. Basic properties and characterizations of soft \(D_μ\)-compact spaces are established. Soft \(D_μ\)-compactness in subspaces of soft generalized topological spaces are also investigated.